Geopolitical Differences and Tax Non-compliance among Yemeni SMEs (Journal of Business Management and Accounting, 2018)
This paper aims at enhancing understanding of tax non-compliance behaviour by investigating the influence of geopolitical differences on taxpayers’ behaviour. The study focuses on income tax compliance behaviour of owner-managers of small and medium enterprises in Yemen. The study was conducted through survey to collect the required data. The major finding of this study is that geopolitical differences has a significant influence on taxpayers’ behaviour. Particularly, the result revealed that the Southern people of Yemen are more compliant with tax rules and regulations than Northern people. This result may be attributed to the geopolitical background of both peoples. While the Southern part of Yemen has been governed by strict socialist regimes, the Northern part was administrated by tribalism system. From the literature, this study may be among the first to consider and provide evidence on the influence of geopolitical differences on the behaviour of taxpayers. The findings of this study could serve as useful input for tax policy and strategy purpose in Yemen.